The impact of transactional leadership on achieving the strategic goals in the schools of the directorate of education in Southern Ghour District - Al-Shaar, Fatima Abdul Halim Abdul Rahman (Journal of Educational and Psychological Sciences, 2021)
This study aimed at identifying the impact of transactional leadership on achieving the strategic goals in the schools of the directorate of education in Southern Ghour District from the perspective of school managers. In order to achieve the study objectives, a 37-item questionnaire was developed; its validity and reliability were verified. The questionnaire was applied to a sample that consisted of (38) male and female managers. After applying the questionnaire, the results revealed that the level of practicing transactional leadership and achieving the strategic goals among the study sample individuals in Southern Ghour District was medium and for all the dimensions. The results revealed that the dimensions of transactional leadership (conditioned rewarding, management except for (the active one)) had an impact on achieving the strategic goals. These dimensions accounted for (76.3%)of total variance in the variable of strategic goals. The results revealed that there is no statistically significant impact for the dimension of (management except for the (passive one)) on achieving the strategic goals. The results also revealed that there are no statistically significant differences attributed to the variables of (gender, educational qualification, experience in management) regarding the level of practicing transactional leadership in the schools of the directorate of education in Southern Ghour District as well as statistically significant differences regarding the level of achieving the strategic goals attributed to the impact of the variable of (educational qualification) in favor of higher studies, and for the variable of (experience in management) in favor of (10 years or more).